OPTIMASI FLOW FEED GAS TERHADAP FLOW AMINE PADA KOLOM CO₂ REMOVAL - Eka Megawati; Yoga Hanggara Pradipta; I Ketut Warsa; Yuniarti Yuniarti (Sekolah Tinggi Teknologi MIGAS, 2022)
The process of liquefying natural gas to produce a product in the form of LPG (Liquefied Petroleum Gas) takes place at a very low temperature of -160ºC. Meanwhile, the gas feed contains a component in the form of carbon dioxide (CO₂) which has a freezing point of -56ºC. The CO₂ separation process is carried out in the CO₂ removal unit which consists of an absorber and an amine regenerator. In the absorber tower, there is a separation process of CO₂ gas components which will be separated by absorption by an amine solution. Amine flow must be adjusted to the flow feed gas that enters the absorber column so that there is no excess amine in the purification process, so the purpose of this study is to determine the maximum value of flow feed gas to get the optimal value of flow amine. The calculation method for finding the maximum flow amine uses trial and error calculations, where the value of the gas flow feed is varied. Based on research can be concluded that, by varying the increase in gas flow feed from 359 m³/h obtained the maximum value of gas flow feed which is 8195 m³/h which produces an optimal flow amine value of 1200,005 m³/h.